The Indian Textile and Clothing Industry: An Economic Analysis - Kar, Mausumi (Springer, 2015)
This book examines the textile and clothing Industry of India and its trade scenario from a global perspective. New developments in international policies related to trade and investment and falling barriers to trade worldwide as well as within individual regional communities have transformed the structure of production and global competition in the textile and apparel industries across the world.